2014
DOI: 10.1177/0013161x14542582
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Dialogue Between Educational Decision Makers and Students of Color

Abstract: Purpose: This article explores the possibilities for reciprocal dialogue between educational decision makers and Students of Color. Such dialogue-defined as interactions in which participants build on each other's words-may provide the means to develop creative ways to address manifestations of systemic racism in education. The article uses the concept of Third Space to investigate how educational decision makers responded to a group of high school Students of Color advocating for change. Research Method: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…Five articles reported that adults had an increased understanding of the experiences and needs of diverse youth because of the project (Brown, ; Galletta & Jones, ; McIntyre, Chatzopoulos, Politi, & Roz, ; Ozer & Wright, ; Sanchez, ). Specifically, adults were more willing to engage in diversity‐related discussions with young people at school (Ozer & Wright, ); relationships between students and teachers were improved (Mitra, ; Voight, ); and adults described engaging in more reflexivity regarding power dynamics between youth and adults (Bertrand, ; McIntyre et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five articles reported that adults had an increased understanding of the experiences and needs of diverse youth because of the project (Brown, ; Galletta & Jones, ; McIntyre, Chatzopoulos, Politi, & Roz, ; Ozer & Wright, ; Sanchez, ). Specifically, adults were more willing to engage in diversity‐related discussions with young people at school (Ozer & Wright, ); relationships between students and teachers were improved (Mitra, ; Voight, ); and adults described engaging in more reflexivity regarding power dynamics between youth and adults (Bertrand, ; McIntyre et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported formalizing opportunities for youth voice into school and community settings (Brazg et al., 2011 Otis & Loeffler, ; Suleiman, Soleimanpour, & London, ). In Bertrand's () study, a YPAR program led to the creation of a “Students Speak Out” group that involved regular opportunities for youth to meet with their principal. Similarly, Ozer and Wright () described several expanded roles for students to be seen as experts, which included: meeting regularly with the principal, informing hiring decisions, providing feedback on teaching practices, and engaging youth of color in back‐to‐school nights.…”
Section: Resultsmentioning
confidence: 99%
“…Also, some educational leadership scholars, including the authors of this piece, have begun to adopt more expansive views of the contributions and viewpoints of youth, parents, and community, especially those marginalized along lines of race or other socially constructed categories (Barajas-López & Ishimaru, 2016; Bertrand, 2014; Fernández & López, 2017; Lac, 2017; López, 2001; Mansfield, 2014; Rodela, 2016; Rogers, Freelon, & Terriquez, 2012). In addition, scholarship beyond the field of educational leadership discusses the contributions of youth, parents, and community in school leadership (Dolan, Christens, & Lin, 2015; Fox et al, 2010; Lozenski, 2016; Morrell, 2006; Quijada Cerecer, Cahill, & Bradley, 2013; Welton et al, 2014).…”
Section: Expanding Conceptions Of Social Justice Educational Leadershipmentioning
confidence: 99%
“…The term “youth voice” is used to describe a variety of ways youth can participate in decision making, ranging from completing surveys to engaging in shared decision making with school administrators and others with official positions of power (Mitra & Gross, 2009). The term is also used in connection with projects involving YPAR (Bertrand, 2014; Lac, 2017; Welton, Harris, La Londe, & Moyer, 2015). Mansfield (2014) has explored youth voice as related to educational leadership.…”
Section: Expanding Conceptions Of Social Justice Educational Leadershipmentioning
confidence: 99%
“…This recognition and promotion of students' heterogeneity is a precedent for third space. Actively and intentionally co-constructing a third space to 125 listen allows concerns to be recognized, but also gives voice to people of color (Bertrand, 2014). Educational policies continue to minimize issues that are occurring in rural, Appalachian areas.…”
Section: Whiteness All Aroundmentioning
confidence: 99%